Witnessed overdoses and naloxone use among visitors to Rikers Island jails trained in overdose rescue. (November 2018) - Huxley-Reicher, Zina; Maldjian, Lara; Winkelstein, Emily; Siegler, Anne; Paone, Denise; Tuazon, Ellenie; Nolan, Michelle L.; Jordan, Alison; MacDonald, Ross; Kunins, Hillary V.
Abstract: With the opioid overdose mortality rates rising nationally, The New York City Department of Health and Mental Hygiene (NYC DOHMH) has worked to expand overdose rescue training (ORT) and naloxone distribution. This study sought to determine rates of overdose witnessing and naloxone use among overdose rescue-trained visitors to the NYC jails on Rikers Island. We conducted a six-month prospective study of visitors to NYC jails on Rikers Island who received ORT. We collected baseline characteristics of study participants, characteristics of overdose events, and responses to witnessed overdose events, including whether the victim was the incarcerated individual the participant was visiting on the day of training. Bivariate analyses compared baseline characteristics of participants who witnessed overdoses to those who did not, and of participants who used naloxone to those who did not. Overall, we enrolled 283 participants visiting NYC's Rikers Island jails into the study. Six months after enrollment, we reached 226 participants for follow-up by phone. 40 participants witnessed 70 overdose events, and 28 participants reported using naloxone. Of the 70 overdose events, three victims were the incarcerated individuals visited on the day of training; nine additional victims were recently released from jail and/or prison. Visitors to persons incarcerated at Rikers Island witness overdose events and are able to perform overdose rescues with naloxone. This intervention reaches a population that includes not only those recently released, but also other people who experienced overdose. Highlights: A 6-month prospective study of NYC jail visitors to Rikers Island trained in naloxone. Of the 283 participants enrolled, 14% witnessed at least one overdose. Of the 283 participants enrolled, 10% administered naloxone at least once. The naloxone use is comparable to similar interventions for high-risk populations. Training jail visitors is effective at reaching a population at risk of overdose.